Achieving high strength and ductility in traditionally brittle soft magnetic intermetallics via additive manufacturing. (November 2019) - Babuska, Tomas F.; Wilson, Mark A.; Johnson, Kyle L.; Whetten, Shaun R.; Curry, John F.; Rodelas, Jeffrey M.; Atkinson, Cooper; Lu, Ping; Chandross, Michael; Krick, Brandon A.; Michael, Joseph R.; Argibay, Nicolas; et al.
Abstract: Intermetallic alloys possess exceptional soft magnetic properties, including high permeability, low coercivity, and high saturation induction, but exhibit poor mechanical properties that make them impractical to bulk process and use at ideal compositions. We used laser-based Additive Manufacturing to process traditionally brittle Fe–Co and Fe–Si alloys in bulk form without macroscopic defects and at near-ideal compositions for electromagnetic applications. The binary Fe–50Co, as a model material, demonstrated simultaneous high strength (600–700 MPa) and high ductility (35%) in tension, corresponding to a ∼300% increase in strength and an order-of-magnitude improvement in ductility relative to conventionally processed material. Atomic-scale toughening and strengthening mechanisms, based on engineered multiscale microstructures, are proposed to explain the unusual combination of mechanical properties. This work presents an instance in which metal Additive Manufacturing processes are enabling, rather than limiting, the development of higher-performance alloys. Graphical abstract: Image 1